Effects of Tacrolimus on Endothelin-1, Melatonin and Heat Shock Protein Levels in Experimental Brain Ischemia - Guler, Ozlem; Yildiz, Mustafa; Bozdemir, Mehmet Nuri; Kavakli, Ahmet; Dagli, Adile Ferda; Ustundag, Bilal (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY